Evaluation of male date palm (Phoenix dactylifera L.) for pollen grain production under arid conditions (Indian Journal of Arid Horticulture, 2018)
In date palm cultivation, pollen grains play an important role for fruit set, maturity, fruit yield and quality. It is a dioceous  plant and pollination is essential for proper fruit set. The farmers of the arid region are facing problem of pollen grains due to lack  of sufficient number and superior type of male plants. Further, it was observed that due to climatic conditions, since last 2-3 years  emergence of spathe is late in males than female palm. The objective of the study was to identify superior genotype of male date  palm for pollen production. Four elite male palms grown at Date palm experimental block, CIAH farm were evaluated during the  year 2016-17 for emergence,, number of spathes, size of spathe and pollens yield/spathe under hot arid environment. The amount  of pollen produced per spathe varied among male palms. The size of spathe was also differed significantly from one male to  another male palm. The pollen production ranged from 17.2 g to 25.0 g per spathe. The study revealed that CIAH/DP/M-03 male  plant produced highest amount of pollen grains (643g/tree) followed by CIAH/DP/M-01 (578g/tree) under arid conditions.
Keywords: Date palm; male; spathes; pollen grains; pollination; fruit set